Pamięć i tajemnica w zbiorowych rytuałach terapeutycznych brazylijskiego candomblé i haitańskiego wodu - Siuda-Ambroziak, Renata (Przegla̜d religioznawczy, 2023)
In the article the author concentrates on an important difference in two contemporary collective therapy rituals involving animal sacrifice in two Afro-Latin-American cults of the same origins: Candomblé in Brazil and Voodoo in Haiti. Looking back at the colonial and early independence context of their evolution in both countries, the author comments on historical, sociocultural factors, which, by influencing collective memory, made Candomblé treat animal sacrifice as something secret or, at least, very discreet, and, at the same time, made Voodoo treat it as an open to all and quite violent public ritual.